2008
DOI: 10.4103/1319-3767.41741
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gastroesophageal reflux disease and its association with Helicobacter pylori infection in chronic renal failure patients and in renal transplant recipients

Abstract: Background/Aims:The prevalence of gastroesophageal reflux disease (GERD) in chronic renal failure patients and in renal transplant recipients (RTR) has been a subject of discussion in the last few years. Our aims are to clarify this association and its relation to Helicobacter pylori infection, and also to identify possible pathogenic factors in the development of this disease in both groups.Methods:The study involved 40 end-stage renal disease (ESRD) patients with upper gastrointestinal (GI) symptoms (group I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 25 publications
2
15
0
1
Order By: Relevance
“…It was seen by Neri et al that those patients who had upper GI symptoms, prior to transplant, were more prone to experience it post-transplant as well [ 6 ]. Mean urea and creatinine in our study was 58.34 ± 39.3 mg/dL and 2.11 ± 1.1 mg/dL respectively, this was higher than that of Saudi Arabia's population, have mean creatinine of 1.6 ± 1.1 mg/dL, but this had no association with factors leading to dyspepsia [ 7 ]. Deranged urea and creatinine, has been considered as one of the known cause of dyspepsia in these patients [ 6 ].…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…It was seen by Neri et al that those patients who had upper GI symptoms, prior to transplant, were more prone to experience it post-transplant as well [ 6 ]. Mean urea and creatinine in our study was 58.34 ± 39.3 mg/dL and 2.11 ± 1.1 mg/dL respectively, this was higher than that of Saudi Arabia's population, have mean creatinine of 1.6 ± 1.1 mg/dL, but this had no association with factors leading to dyspepsia [ 7 ]. Deranged urea and creatinine, has been considered as one of the known cause of dyspepsia in these patients [ 6 ].…”
Section: Discussionmentioning
confidence: 66%
“…A study done at Istanbul also finds gastritis as the most common finding on endoscopy, seen in 55 (85.9%) patients [ 15 ]. Abdur Rehman and Al Qurain's observation was contrasting and found that GERD was more common in renal transplanted patients in comparison with gastritis [ 7 ]. In our study frequency of H. Pylori was less as compare to the other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Why H.pylori infection is low in dialysis patients in spite of their immune-compromised status is not very clear. In an attempt to find an explanation, Teenan et al, 18 Davenport et al 17 and Abdul-Rahman et al 58 61 They found that after six weeks of intermittent hemodialysis, in vitro T-cell proliferation on stimulation improved significantly (stimulation index, 21.6 +/-18.5 vs 58.1 +/-45.5; P<0.01). This improvement occurred regardless of whether synthetic dialyzers or cellulose membranes were used for the initiation of dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Bildirilen insidansı araştırma yöntemine bağlı olarak % 12 ile % 55 arasında değişmektedir (1,2,3).Özellikle retrosternal yanma ve regürjitasyon, son dönem böbrek hastalığı (SDBH) olanlarda ve renal transplant alıcılarında sık görülen bulgular olup, bu şikayetler gastroözofageal reflü hastalığına bağlı olabilir (4,5). Bu hasta gruplarında gastroözofageal reflü hastalığının (GÖRH) prevalansı son birkaç yıldır tartışılmaya başlamıştır ve bu durum hakkında çok az bilgi mevcuttur (6). GÖRH gastrik içeriğin yemek borusuna geri dönüşü olarak tanımlanır.…”
Section: Introductionunclassified